Relationship between Milk Yield and Udder Morphology Traits in White Fulani Cows - Oladipupo Ridwan Bello; Adebowale Emmanuel Salako; Adebayo Samson Akinade; Maaruf Yakub (Dairy, 2023)
The study examined the relationship between milk yield and udder morphology traits in White Fulani cows. Fifty-eight apparently healthy cows in early lactation at 2nd, 3rd, and 4th parity were used in the study. The data obtained from the cows were test day milk yield (TDMY) from single milking and udder morphology traits comprising udder length (UL), udder width (UW), udder depth (UD), fore teat length (FTL), rear teat length (RTL), fore teat diameter (FTD), and rear teat diameter (RTD). There was no significant effect of parity on TDMY or the udder morphology traits. Phenotypic correlations between TDMY, UL, UW, and UD were positive and significant. Notably, phenotypic correlations between UL and TDMY at different parities were the strongest. Teat measurements had no significant correlation with TDMY. Stepwise and principal component regressions were implemented to assess the relationship between milk yield and udder morphology traits. Interestingly, UL was the only trait that entered the reduced models. The results suggest a probable genetic correlation between milk yield and udder length. Therefore, since udder conformation traits are heritable, when selecting for udder length in White Fulani cows, a correlated response in milk yield is expected.